2013
DOI: 10.1038/ncomms3825
|View full text |Cite
|
Sign up to set email alerts
|

A closed-loop synthetic gene circuit for the treatment of diet-induced obesity in mice

Abstract: Diet-induced obesity is a lifestyle-associated medical condition that increases the risk of developing cardiovascular disease, type 2 diabetes and certain types of cancer. Here we report the design of a closed-loop genetic circuit that constantly monitors blood fatty acid levels in the setting of diet-associated hyperlipidemia and coordinates reversible and adjustable expression of the clinically licensed appetite-suppressing peptide hormone pramlintide. Grafting of the peroxisome proliferator-activated recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 55 publications
1
104
0
3
Order By: Relevance
“…Similarly as in other studies, 13 the dynamic range of the genetic circuit in the in vivo conditions did not fully recapitulate the in vitro setting, but nevertheless we have demonstrated that the device enabled a reasonable FI with a relatively low leakage when measuring SEAP as an output (Figures 4E and 4F). When therapeutic proteins were profiled in the serum or peritoneal lavage fluid of mice, a better dynamic range was observed, which was attributed to the lower background ( Figures 5C and 5D).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Similarly as in other studies, 13 the dynamic range of the genetic circuit in the in vivo conditions did not fully recapitulate the in vitro setting, but nevertheless we have demonstrated that the device enabled a reasonable FI with a relatively low leakage when measuring SEAP as an output (Figures 4E and 4F). When therapeutic proteins were profiled in the serum or peritoneal lavage fluid of mice, a better dynamic range was observed, which was attributed to the lower background ( Figures 5C and 5D).…”
Section: Discussionsupporting
confidence: 54%
“…10,11 These cells can act as prosthetic devices, which do not require any host genome modification. Of particular interest are sensor-effector designs that can autonomously detect and treat various pathological conditions, such as a malfunction in urate homeostasis, 12 diet-induced obesity, 13 and diabetic ketoacidosis. 14 Recently, an innovative designer cell device to treat experimental psoriasis by converting the disease-relevant inputs into the therapeutic output was presented.…”
Section: Introductionmentioning
confidence: 99%
“…for the treatment of gout, metabolic syndrome, and obesity in mice (36,37,43). In this study, we designed a thyroid hormone homeostasis circuit that enables the restoration of the physiological hypothalamus-pituitary-thyroid axis in a mouse model of experimental Graves' disease.…”
Section: Synthetic Gene Network Have Reached a Level Of Sophisticatimentioning
confidence: 99%
“…Most importantly, increasing amounts of dietary fat led to an enhanced release of pramlintide that resulted in reduced eating and body weight in mice on a high-fat but not on a low-fat diet. 118 Whether this strategy can be employed clinically needs to be studied in coming years.…”
Section: Amylin As a Potential Treatment Strategy Against Obesitymentioning
confidence: 99%
“…118 The authors of this study produced a self-controlled release device for the amylin analog pramlintide. Cells were manipulated in a way that they contained a closed-loop genetic circuit that constantly monitored blood fatty acid levels, and that was coupled to the coordinated and reversible expression and release of pramlintide.…”
Section: Amylin As a Potential Treatment Strategy Against Obesitymentioning
confidence: 99%